Studi Eksperimental Diameter Lubang Nozzle Dan Laju Aliran Volumetrik Udara TerhadapTemperatur Nyala Api Kompor Berbahan Bakar Oli Bekas - Hamim, Mohammad Rohman; Adiwidodo, Satworo (Energy - Jurnal Ilmiah Ilmu-Ilmu Teknik, 2024)
The utilization of used oil into fuel has begun to be used today even though only some people. Knowing how the interaction of nozzle hole diameter on fire temperature in portable stoves. In this study used experimental research, by testing the value of the independent variable with (nozzle hole diameter (2, 3, 4) and variation of air volumetric flow rate, the response obtained (dependent variable) knowing the causal relationship of the study. This research processing method uses factorial ANOVA. see the interaction between independent variables on the dependent variable in addition to seeing the effect of independent variables on the dependent variation. The flame that produces the highest temperature 900C in the 3mm hole diameter variation by having an air flow rate of 0.004 mᶟ/s. The flame with T1 varies the diameter of the 4mm hole with the speed of the air flow rate at 0.006 mᶟ/s. Then the T2 flame has decreased graphically from the previous diameter at 3 mm hole diameter with air volumetric flow velocity at 0.006 mᶟ/s. The larger the hole, the smaller the air pressure, otherwise if the smaller the diameter of the nozzle hole, the greater the pressure spread into the combustion chamber is better.